Academic Well-Being of University Students with Disability: Role of Hardiness and Social Support - Arthur Huwae; Alessandra Florensya Saija; Dennys Christovel Dese (Journal An-Nafs: Kajian Penelitian Psikologi, 2022)
Online learning during the COVID-19 pandemic seems to produce a new challenge for students with disabilities. The physical limitations experienced demand an adjustment to a digitalization-based system. These changes are pros and cons for university students with disabilities to achieve well-being through success in the academic field. The achievement of academic well-being of university students with disabilities seems inseparable from internal and external factors. Based on the phenomena, this study aims to determine the role of hardiness and social support (family, friends, and significant others) on the academic well-being of students with disabilities. The method used quantitative with a multiple regression design. The participants were 184 university students with physical disabilities using the snowball sampling technique. The research scale consists of a hardiness scale, a social support scale, and an academic well-being scale. The results of the study indicated that the hardiness and social support affected the academic well-being of university students with disabilities. The achievement of academic well-being experienced by university students with disabilities provides a new understanding that self-limitation does not make it an obstacle to forming a good self-concept, forming a self-strategy in overcoming online learning problems, and increasing productivity in every educational process undertaken. Thus, hardiness and social support factors play an important role in realizing the academic well-being of university students with disabilities